Using monazite and zircon petrochronology to constrain the P–T–t evolution of the middle crust in the Bhutan Himalaya. (2nd June 2016) - Regis, D.; Warren, C. J.; Mottram, C. M.; Roberts, N. M. W.
Abstract: The growth and dissolution behaviour of accessory phases (and especially those of geochronological interest) in metamorphosed pelites depends on, among others, the bulk composition, the prograde metamorphic evolution and the cooling path. Monazite and zircon are arguably the most commonly used geochronometers for dating felsic metamorphic rocks, yet crystal growth mechanisms as a function of rock composition, pressure and temperature are still incompletely understood. Ages of different growth zones in zircon and monazite in a garnet‐bearing anatectic metapelite from the Greater Himalayan Sequence in NW Bhutan were investigated via a combination of thermodynamic modelling, microtextural data and interpretation of trace‐element chemical 'fingerprint' indicators in order to link them to the metamorphic stage at which they crystallized. Differences in the trace‐element composition (HREE, Y, EuN /Eu*N ) of different phases were used to track the growth/dissolution of major (e.g. plagioclase, garnet) and accessory phases (e.g. monazite, zircon, xenotime, allanite). Taken together, these data constrain multiple pressure–temperature–time ( P–T–t ) points from low temperature (<550 °C) to upper amphibolite facies (partial melting, >700 °C) conditions. The results suggest that the metapelite experienced a cryptic early metamorphic stage at c . 38 Ma at <550 °C, ≥0.85 GPa during which plagioclase was probably absent. This was followed by a prolonged high‐ T, medium‐pressure ( 600 °C, 0.55 GPa) evolution at 35–29 Ma during which the garnet grew, and subsequent partial melting at >690 °C and >18 Ma. Our data confirm that both geochronometers can crystallize independently at different times along the same P–T path and that neither monazite nor zircon necessarily provides timing constraints on 'peak' metamorphism. Therefore, collecting monazite and zircon ages as well as major and trace‐element data from major and accessory phases in the same sample is essential for reconstructing the most coherent metamorphic P–T–t evolution and thus for robustly constraining the rates and timescales of metamorphic cycles.